A pitfall in the cytodiagnosis of sputum of asthmatics - Naylor, Bernard (1964)
The sputum of an asthmatic often contains large, well-circumscribed clusters of benign columnar epithelial cells which can be misinterpreted as papillary fragments of an adenocarcinoma. Their presence is a manifestation of the excessive shedding of the mucosa of the lower respiratory tract accompanying an attack of bronchial asthma. These clusters are illustrated and compared with clusters of adenocarcinoma cells. To discriminate between the two types of cluster may be difficult and it is therefore important for the cytologist to know when a sputum is from an asthmatic.